An Automated Hydrographic Survey in James Bay, Canada - MacDonald, G. D. (The International Hydrographic Review, 2015)
This paper describes the successful use of the Canadian automated system HAAPS (Hydrographic Acquisition And Processing System) in a 1973 survey of a shipping corridor.